Engaging theories in interpersonal communication multiple perspectives - Braithwaite, Dawn O.; Schrodt, Paul (Routledge, an imprint of the Taylor & Francis Group, 2022)
"The third edition of this text maintains its place as a key resource for learning the foundational and emerging theories in the field of interpersonal communication. With each chapter devoted to a specific theory and authored by an expert in that theory, the book gives students a comprehensive overview of this discipline. This edition features an expanded discussion of theory evaluation and theory development and new attention to both social media and diversity. With the theory chapters sharing the same structure, the book ensures consistent coverage of topics within each theory. This book is an essential text for advanced undergraduate and graduate courses in interpersonal communication and theory."--Provided by publisher.